Development of Understanding and Ability to Used Technology for Learning Application on “LIMIT OF FUNCTION” of Mathayomsuksa 6 Students by Using the Minicourse Learning Packaged - Tanyarattanasrisakul, Mathasit (Journal of Humanities, Social Sciences, and Arts, 2022)
The objective of this research were to 1) compare the understanding on concept of limit function of Mathayomsuksa 6 students before and after learned by minicourse learning packaged and 2) study the ability to used technology for learning application on limit of function of Mathayomsuksa 6 students after learned by minicourse learning packaged. The samples were 41 Mathayomsuksa 6 students (class 4) at the first semester of academic year 2019 of Rachineeburana School, Nakhon Pathom province. Research design used applied the quasi-experimental design with one-group pretest-posttest design. The research instrument comprising of minicourse learning packaged, conceptual understanding test, and evaluation form of ability to used technology for learning. Data analyzes used applied were percentage, arithmetic mean, standard deviation, and t-test for dependent. The research results showed that; 1) The understanding on concept of limit function of Mathayomsuksa 6 students after learned by minicourse learning packaged was higher than before at .05 statistical significantly level and 2) The ability to used technology for learning application on limit of function of Mathayomsuksa 6 students after learned by minicourse learning packaged was a good level.